2001
DOI: 10.1088/0953-2048/14/10/301
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical studies of the uniform critical state in bulk MgB2

Abstract: We present a detailed magneto-optical investigation of the magnetic flux penetration in polycrystalline MgB 2 slabs made by direct reaction of B and Mg. Our results unambiguously indicate a uniform, Bean critical state magnetization behavior with almost no electromagnetic granularity. From the measured magnetic flux profiles we were able to extract the temperature dependence of the critical current density J c (T). The J c (T) value reaches 1.8×10 5 A/cm 2 at 10K and 0.12T, in good agreement with global magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Given these promising results combined with weak current blocking by grain boundaries [97], the lack of electromagnetic granularity [98], and very slow thermally-activated flux creep [99,100], it is not surprising that MgB 2 is being regarded as a strong contender of traditional high-field magnet materials like NbTi and Nb 3 Sn. Despite these achievements, a detailed theory of pinning in MgB 2 is trill lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Given these promising results combined with weak current blocking by grain boundaries [97], the lack of electromagnetic granularity [98], and very slow thermally-activated flux creep [99,100], it is not surprising that MgB 2 is being regarded as a strong contender of traditional high-field magnet materials like NbTi and Nb 3 Sn. Despite these achievements, a detailed theory of pinning in MgB 2 is trill lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The relative lower J c in this study may be due to the fact A magneto-optical image of an air quenched MgB 2 slab demonstrates that almost no spatial variation of J c is visible. 2,18 This suggests that there is no inherent string suppression of current across the grain boundaries. Obviously, the current percolation behavior in the quenched MgB 2 is determined by the nanodomains that constituted the subgrains in the clusters.…”
mentioning
confidence: 99%
“…around entire regions consisting of many tiny grains, indicating a lack of any weak links between the grains. Many subsequent studies have confirmed this conclusion [24]- [26]. Subsequent experiments [27] have found that it is even possible to obtain high J c values in powder-in-tube wires by rolling without subsequent sintering.…”
Section: J C and Flux Pinningmentioning
confidence: 82%